KAMPANYE PROGRAM GENRE MOVE ON DALAM MEMAKSIMALKAN USIA PRODUKTIF DI KABUPATEN KAMPAR - Mariska Amniah Riva; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Indonesia is currently experiencing a demographic bonus. This is marked by a doubling in the number of productive age populations accompanied by a delay in the growth of young age populations and a smaller number of elderly residents. Even though the number of adolescents of productive age is very large, the common problems faced by adolescents who do not have the life skills to understand they have not been handled optimally. And life skills alone will be useful for productive age teenagers to prepare for their future plans. Therefore, the GenRe Ambassador of Indonesia 2018, the educational pathway initiated a GenRe Move On program in which this program is needed to overcome the problems of adolescent groups and maximize the productive age of adolescents to plan for their future. The purpose of this study is to determine the campaign planning, campaign implementation, and campaign obstacles that occur in the GenRe Move On campaign program.   This study used qualitative research methods. The research informants totaling of nine people according to the criteria selected using a purposive technique. Data collection techniques consist of interviews, observation and documentation. While the data analysis technique uses descriptive analysis according to Miles and Huberman. The data validity checking technique uses an extension of participation and triangulation.         The results showed that this program's campaign planning aims to fortify adolescents with positive things and activities so as to avoid things that destroy the future of adolescents, the target in the GenRe Move On program is adolescents aged 10-24 years who are not married, the message conveyed the GenRe Move On program is the GenRe Triad, which is to avoid early marriage, premarital sex and drug abuse and drug use and other material based on syllabus or modules given by the GenRe Ambassador coordinator entitled "Rencanakan Masa Depanmu". The media used is to use mass media in the form of print media, electronic media and social media which aims to disseminate information about programs and activities organized in GenRe Move On program. There are also several GenRe Move On campaigns such as socialization, GenRe On Street and Gempor, and obstacles that occur such as lack of attention from the audience, differences of opinion and transportation barriers. Keyword: Campaign, Demographic Bonus, Productive Ages